Clinical outcomes of percutaneous coronary intervention for acute coronary syndrome between hospitals with and without onsite cardiac surgery backup. Issue 1 (January 2017) - Akasaka, Tomonori; Hokimoto, Seiji; Sueta, Daisuke; Tabata, Noriaki; Oshima, Shuichi; Nakao, Koichi; Fujimoto, Kazuteru; Miyao, Yuji; Shimomura, Hideki; Tsunoda, Ryusuke; Hirose, Toyoki; Kajiwara, Ichiro; et al.
Abstract: Background: Based on the 2011 American College of Cardiology/American Heart Association percutaneous coronary intervention (PCI) guideline, it is recommended that PCI should be performed at hospital with onsite cardiac surgery. But, data suggest that there is no significant difference in clinical outcomes following primary or elective PCI between the two groups. We examined the impact of with or without onsite cardiac surgery on clinical outcomes following PCI for acute coronary syndrome (ACS). Methods and results: From August 2008 to March 2011, subjects ( n  = 3241) were enrolled from the Kumamoto Intervention Conference Study (KICS). Patients were assigned to two groups treated in hospitals with ( n  = 2764) or without ( n  = 477) onsite cardiac surgery. Clinical events were followed up for 12 months. Primary endpoint was in-hospital death, cardiovascular death, myocardial infarction, and stroke. And we monitored in-hospital events, non-cardiovascular deaths, bleeding complications, revascularizations, and emergent coronary artery bypass grafting (CABG). There was no overall significant difference in primary endpoint between hospitals with and without onsite cardiac surgery [ACS, 7.6% vs. 8.0%, p  = 0.737; ST-segment elevation myocardial infarction (STEMI), 10.4% vs. 7.5%, p  = 0.200]. There was also no significant difference when events in primary endpoint were considered separately. In other events, revascularization was more frequently seen in hospitals with onsite surgery (ACS, 20.0% vs. 13.0%, p  < 0.001; STEMI, 21.9% vs. 14.5%, p  = 0.009). We performed propensity score matching analysis to correct for the disparate patient numbers between the two groups, and there was also no significant difference for primary endpoint (ACS, 8.6% vs. 7.5%, p  = 0.547; STEMI, 11.2% vs. 7.5%, p  = 0.210). Conclusions: There is no significant difference in clinical outcomes following PCI for ACS between hospitals with and without onsite cardiac surgery backup in Japan.